Rola i właściwość sądów powszechnych i administracyjnych w sprawach antymonopolowych w świetle najnowszego orzecznictwa i zmian normatywnych: [The role and the jurisdiction of Civil and Administrative Courts in antimopoly cases in the light of the latest case-law and normative amendments] (Studia Prawnicze / The Legal Studies, 2017)
Zamierzeniem artykułu jest przede wszystkim pokazanie ustaleń w zakresie właściwości sądowej w sprawach antymonopolowych w świetle ostatnich zmian legislacyjnych oraz najnowszego orzecznictwa. W ostatnim okresie problematyka jurysdykcji sądów w sprawach antymonopolowych była przedmiotem dyskusji naukowej oraz była przedmiotem pewnych przemian legislacyjnych, które jednak dalekie były od pierwotnych projektów. Dodatkowo rozwijające się orzecznictwo Sądu Najwyższego także wpłynęło na postrzeganie roli i właściwości SOKiK w sprawach antymonopolowych. Co także istotne, sądy administracyjne również kontynuują swoje orzecznictwo w wybranych aspektach spraw antymonopolowych i można nawet mówić o pewnej stabilizacji linii orzeczniczych. The article presents the latest developments in jurisprudence and the law in relation to the role and the jurisdiction of courts in the antimonopoly cases. The basic assumption of the article is that there exist parallel jurisdiction of civil and administrative courts in competition cases and sometimes it is hard to determine which court is competent to hear particular competition case. The article begins with an analysis of recent changes in the law that influenced jurisdiction of the antimonopoly court. It is followed by the discussion of the latest Supreme Court jurisprudence concerning the role of the antimonopoly court. The next analyzed issue is the identification of all administrative acts issued by the antimonopoly authority together with determination which court is competent to hear appeals against each of them. It provides a good background for a detailed analysis of non-typical acts of the antimonopoly authority with an attempt to clarify which court has jurisdiction over them. The article concludes with critical observation that parallel jurisdiction of civil and administrative courts in competition cases is a source of constant problems. Especially civil courts tend to ignore the fact that administrative court do play a role in competition cases simply because civil courts do not poses legal tools to offer judicial protection for addressees of certain types of actions of the antimonopoly authority.